2011
DOI: 10.1111/j.1349-7006.2011.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of estrogen receptor‐α in human papillary thyroid carcinomas studied by laser‐capture microdissection and molecular biology

Abstract: The expression pattern of estrogen receptor (ER) isoforms in normal and tumor thyroid tissues is still controversial and poor defined, therefore, a more detailed study of the distribution of these molecules is needed. Most discrepancies might be due to the methods utilized. We studied the expression of ER isoforms in human papillary thyroid carcinoma (PTC), in fine‐needle aspiration biopsy‐derived specimens, and in cells, using more accurate techniques, such as laser‐capture microdissection, real‐time quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 28 publications
4
34
0
1
Order By: Relevance
“…Thyroid stem and progenitor cells derived from thyroid nodules express ERa and ERb with eight times higher expression levels of ERa compared with normal thyroid cells . This high ERa expression in undifferentiated stem/progenitor cells is reminiscent of the above-mentioned overexpression of ERa in some papillary thyroid carcinomas (Di Vito et al 2011). High expression levels of ERa in thyroid stem/progenitor cells were further upregulated by stimulation with E 2 , which is in accordance with findings for human benign and malignant thyroid cells (Manole et al 2001.…”
Section: Endocrine-related Cancersupporting
confidence: 79%
See 1 more Smart Citation
“…Thyroid stem and progenitor cells derived from thyroid nodules express ERa and ERb with eight times higher expression levels of ERa compared with normal thyroid cells . This high ERa expression in undifferentiated stem/progenitor cells is reminiscent of the above-mentioned overexpression of ERa in some papillary thyroid carcinomas (Di Vito et al 2011). High expression levels of ERa in thyroid stem/progenitor cells were further upregulated by stimulation with E 2 , which is in accordance with findings for human benign and malignant thyroid cells (Manole et al 2001.…”
Section: Endocrine-related Cancersupporting
confidence: 79%
“…Again, other immunohistochemical studies showed similar ERa staining in normal thyroid and tumor tissues (Hampl et al 1985, Vaiman et al 2010a. Recently, in papillary thyroid carcinomas, overexpression of ERa but lack of ERa expression in the surrounding tissue and absence of ERb expression in the tumor samples have been described (Di Vito et al 2011). These authors used the sensitive technique of laser capture microdissection to isolate homogeneous cell population from PTC surgical samples to analyze ERa and ERb expression.…”
Section: Er Expression In Benign and Malignant Thyroid Tissuesmentioning
confidence: 99%
“…A predominant expression of ERa was also observed in other stem and progenitor cells (Hu et al 2011, Matsubara & Matsubara 2012. Furthermore, overexpression of ERa was also reported in papillary thyroid carcinomas (Di Vito et al 2011). Effects of E 2 on BrdU incorporation in human thyroid stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Benign and malignant thyroid cells and tissues express functional oestrogen receptors (ERs) and their growth is stimulated by oestrogen (Furlanetto et al 1999, Manole et al 2001, Ceresini et al 2006, Kumar et al 2010, Rajoria et al 2010, Di Vito et al 2011. In addition, the presence of these receptors has also been demonstrated in thyroid vessels that may be relevant for the vascularization of neoplastic tissues (Ceresini et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors are responsible for the functions of estrogen, and they have opposite functions with respect to cell proliferation and survival. ERa acts as a stimulator of proliferation and suppressor of apoptosis, whereas ERb acts as an adjuvant for cell differentiation and stimulates apoptosis (Di Vito et al 2011). Investigations with thyroid cancer cell lines and also some human thyroid tumors have demonstrated the expression of ERs in thyroid tumor cells, both neoplastic and non-neoplastic, indicating that thyroid cells are likely to experience effects of estrogen or ERs (Lee et al 2005, Zeng et al 2007.…”
Section: Endocrine-related Cancermentioning
confidence: 99%